ChemInform Abstract: Copper Polytellurite‐Chlorides with A2+ Cations (A: Cd, Pb) Obtained by CVT Reactions. Issue 41 (September 2016) - Zinyakhina, Diana O.; Siidra, Oleg I.; Charkin, Dmitri O.; Nazarchuk, Evgeniy V.; Bubnova, Rimma S.
Abstract: Single crystals of Pb5 Cu2 (Te4 O11 )Cl8 (I) and CdCu2 (Te3 O8 )Cl2 (II) are obtained by chemical vapor transport reactions of either a 3:1:1 mixture of CuCl2, TeO2, and PbO or a 1:2:1 mixture of CuCl2, TeO2, and CdO (evacuated quartz tube, 450→430 °C, 24 h).